KEANEKARAGAMAN JENIS DAN STRUKTUR TEGAKAN TINGGAL DI AREAL KERJA PT SARPATIM PROVINSI KALIMANTAN TENAH : H e r i a n t o - Admin JHT (Jurnal Hutan Tropika, 2017)
ABSTRACK Logging activities have an impact on changes in composition and standing structure, tree species distribution, community similarity and species diversity. This study was aimed to determine the diversity of structures and composition of trees at the logged-over forests. Area of study was located at annual Block of 2005, 2010, and 2015 of forest concession (IUPHHK-HA) PT Sarpatim in Central Kalimantan Province. Data was collected at 2017. The results showed that the composition and structure of the stands are ecologically different, which is indicated by the low type of species equality index. The stands at the level of seedlings, sapling, poles and trees from each location are almost all different. But there are some of the same types encountered dominating on the block locations of 2005, 2010 and 2015 such as Shorea leprosula, Dipterocarpus borneensis, Shorea laevis, Litsea sp. The stand density at the 2005 block location is higher than the two sites in 2010 and 2015, while the location of 2015 is the location with the lowest stand density. Keywords Composition, density, diversity, standing structure.